2007
DOI: 10.1128/jb.01782-06
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Adaptation to Nitrosative Stress inBacillus subtilis

Abstract: Bacteria use a number of mechanisms for coping with the toxic effects exerted by nitric oxide (NO) and its derivatives. Here we show that the flavohemoglobin encoded by the hmp gene has a vital role in an adaptive response to protect the soil bacterium Bacillus subtilis from nitrosative stress. We further show that nitrosative stress induced by the nitrosonium cation donor sodium nitroprusside (SNP) leads to deactivation of the transcriptional repressor NsrR, resulting in derepression of hmp. Nitrosative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 43 publications
(46 reference statements)
0
56
2
1
Order By: Relevance
“…In the presence of oxygen, the Hmp enzyme acts as an NO scavenger and is responsible for the direct detoxification of NO to nitrate (35,79). Furthermore, it has been shown that hmp mutants of B. subtilis and S. aureus, as well as of Salmonella enterica and E. coli, are hypersensitive to NO-related killing (59,83,84,89). Thus, the upregulation of Hmp is a central feature of NO stress adaptation in both B. subtilis and S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of oxygen, the Hmp enzyme acts as an NO scavenger and is responsible for the direct detoxification of NO to nitrate (35,79). Furthermore, it has been shown that hmp mutants of B. subtilis and S. aureus, as well as of Salmonella enterica and E. coli, are hypersensitive to NO-related killing (59,83,84,89). Thus, the upregulation of Hmp is a central feature of NO stress adaptation in both B. subtilis and S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…NO oxidation to nitrite and nitrate is also facilitated by transition metals and intracellular enzymes, e.g. by flavohemoglobin and truncated hemoglobin (25)(26)(27)(28)(29). Thus, the level of nitrite and nitrate in the medium indirectly reflects NOS activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, it would be expected that this ArsR-like protein plays an important role in regulating norB during infection, when iron is limiting and Fur would not always be bound to its operator. It has recently been shown that NsrR controls the expression of NO detoxification systems in several pathogenic and environmental organisms, and that genes in the NsrR regulon contribute to resistance to nitrosative stress (Rodionov et al, 2005;Overton et al, 2006;Filenko et al, 2007;Gilberthorpe et al, 2007;Rock et al, 2007;Rogstam et al, 2007). NsrR also regulates NO metabolism in N. meningitidis, and meningococcal reduction of NO produced by activated macrophages has been shown to greatly modulate the resulting cytokine and chemokine response, enhance intracellular survival and inhibit macrophage apoptosis (Stevanin et al, 2005Tunbridge et al, 2006).…”
Section: Discussionmentioning
confidence: 99%